2022
DOI: 10.3389/fphys.2022.1006427
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs as potential biomarkers and therapeutic targets in polycystic kidney disease

Abstract: Polycystic kidney disease (PKD) is a significant cause of end-stage kidney failure and there are few effective drugs for treating this inherited condition. Numerous aberrantly expressed non-coding RNAs (ncRNAs), particularly microRNAs (miRNAs), may contribute to PKD pathogenesis by participating in multiple intracellular and intercellular functions through post-transcriptional regulation of protein-encoding genes. Insights into the mechanisms of miRNAs and other ncRNAs in the development of PKD may provide nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Kidney cysts in mouse and human ADPKD have increased renal expressions of miR-17, which represses oxidative phosphorylation and FAO by inhibiting peroxisome proliferator-activated receptor alpha (PPARα), a regulator of lipid metabolism [ 58 ]. Mitochondrial fatty-acid β-oxidation (FAO) is reduced in cell lines derived from ADPKD mouse models and leads to increase fatty-acid biosynthesis [ 59 , 60 ].…”
Section: New Biomarkers In Adpkdmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney cysts in mouse and human ADPKD have increased renal expressions of miR-17, which represses oxidative phosphorylation and FAO by inhibiting peroxisome proliferator-activated receptor alpha (PPARα), a regulator of lipid metabolism [ 58 ]. Mitochondrial fatty-acid β-oxidation (FAO) is reduced in cell lines derived from ADPKD mouse models and leads to increase fatty-acid biosynthesis [ 59 , 60 ].…”
Section: New Biomarkers In Adpkdmentioning
confidence: 99%
“…These findings indicate that the dysfunctional miRNA expression in the cystic epithelial cells is an indispensable factor in the development of PKD due to its multiple roles in disease pathogenesis: oxidative stress in mitochondrial metabolism, dysregulated cell proliferation, autophagy and apoptosis, inflammation, fibrosis, cell-to-cell contact via extracellular vesicles, and exosomes [ 59 , 80 ].…”
Section: New Biomarkers In Adpkdmentioning
confidence: 99%
“…Studies have demonstrated the presence of altered extracellular vesicles profiles, in term of their nucleic acid and protein content, in various renal diseases including ADPKD 11,21 . The extracellular vesicles content, specifically small non‐coding RNAs, are considered to play a role in the pathogenesis of ADPKD by influencing various signaling pathways through the post‐transcriptional control of related genes 22 . The pathologically modified extracellular vesicles profiles may provide potential biomarkers for disease diagnosis, prognosis and monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…11,21 The extracellular vesicles content, specifically small non-coding RNAs, are considered to play a role in the pathogenesis of ADPKD by influencing various signaling pathways through the post-transcriptional control of related genes. 22 The pathologically modified extracellular vesicles profiles may provide potential biomarkers for disease diagnosis, prognosis and monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic underpinnings of PLD suggest the presence of a primary pathogenic germline variant in a PLD gene, and a secondary pathogenic somatic variant [ 1 , 3 , 9 , 12 , 13 , 14 , 15 ]. The consequences of these variants involve many molecular pathways, and a wide range of factors have been suggested including (but not limited to) cAMP, estrogen, primary cilia dysfunction, bile acid levels, cell–matrix remodeling, epigenetics, post-translational modifications, autophagy, and aberrant proteostasis [ 2 , 3 , 8 , 9 , 10 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. This range of factors has resulted in a large variety in the potential targets for therapeutic treatment [ 2 , 3 , 8 , 9 , 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%